2003
DOI: 10.1128/aem.69.3.1521-1526.2003
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Abundance of Total and Pathogenic Vibrio parahaemolyticus in Alabama Oysters

Abstract: Recent Vibrio parahaemolyticus outbreaks associated with consumption of raw shellfish in the United States focused attention on the occurrence of this organism in shellfish. From March 1999 through September 2000, paired oyster samples were collected biweekly from two shellfish-growing areas in Mobile Bay, Ala. The presence and densities of V. parahaemolyticus were determined by using DNA probes targeting the thermolabile hemolysin (tlh) and thermostable direct hemolysin (tdh) genes for confirmation of total a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
284
10
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(332 citation statements)
references
References 32 publications
32
284
10
6
Order By: Relevance
“…The tdh gene was detected in four strains, and trh was detected in 23 strains (Figure 2). Several studies have suggested a strong influence of temperature on the concentration of vibrio in marine waters [27][28][29][30] . However, this study only established a correlation with V. vulnifi cus (p < 0.05).…”
Section: Seawater Parametersmentioning
confidence: 99%
“…The tdh gene was detected in four strains, and trh was detected in 23 strains (Figure 2). Several studies have suggested a strong influence of temperature on the concentration of vibrio in marine waters [27][28][29][30] . However, this study only established a correlation with V. vulnifi cus (p < 0.05).…”
Section: Seawater Parametersmentioning
confidence: 99%
“…V. parahaemolyticusmediated gastroenteritis has traditionally been associated with two virulence factors, thermostable direct hemolysin (TDH) and TDH-related hemolysin, which are present in most clinical isolates and have been detected with low frequency in environmental strains (DePaola et al, 2003;Dileep et al, 2003). The relationship between strains isolated from the aquatic environment, considered the source of the infection, and strains isolated from clinical cases is poorly understood.…”
mentioning
confidence: 99%
“…In the marine and estuarine environments, V. parahaemolyticus must navigate changing salinities, temperatures, and nutrient limitations and is known to proliferate during the warmer months of the year when the salinity and temperature are elevated (2,(5)(6)(7)(8)(9). Vibrio parahaemolyticus levels in marine and estuarine waters are linearly dependent on both salinity and water temperature, and in the winter, the bacterium is rarely isolated from the water column and is typically only found in small numbers in sediment (2,5,10).…”
mentioning
confidence: 99%